The status of the Arabic language in the Constitution of the Republic o f Iraq for the year 2005: A comparative study - حسين, كمال علي (Journal of Legal Sciences, 2020)
The Constitution of the Republic of Iraq for the year 2005, in force and following most of the previous Iraqi constitutions and the constitutions of the Arab countries, states that Arabic is the official language of the state.  Recognition of the great and lofty status of it, it is the language sanctified by the Creator (Almighty), by choosing a language not written by Heaven and the dominant of them all (the Holy Quran).  In addition, it is also the endowment of lingual to the seal of his prophets and the leader of his messengers, the greatest Prophet Muhammad bin Abdullah (peace be upon him).  Moreover, this is what questioned the study of the rules of this constitutional demarcation of the Arabic language in Iraq.  In addition to the relevant legislation, it examines the special constitutional status of the other language in Iraq such as Kurdish, Syriac, Turkmen and Armenian. As they share the Arabic language with Arabic (the languages) of the other partners with Arabic speakers in the broad spectrum of Iraq.